Multiplex sequencing of bacterial artificial chromosomes for assembling complex plant genomes. Issue 7 (23rd January 2016) - Beier, Sebastian; Himmelbach, Axel; Schmutzer, Thomas; Felder, Marius; Taudien, Stefan; Mayer, Klaus F. X.; Platzer, Matthias; Stein, Nils; Scholz, Uwe; Mascher, Martin
Summary: Hierarchical shotgun sequencing remains the method of choice for assembling high‐quality reference sequences of complex plant genomes. The efficient exploitation of current high‐throughput technologies and powerful computational facilities for large‐insert clone sequencing necessitates the sequencing and assembly of a large number of clones in parallel. We developed a multiplexed pipeline for shotgun sequencing and assembling individual bacterial artificial chromosomes (BACs) using the Illumina sequencing platform. We illustrate our approach by sequencing 668 barley BACs ( Hordeum vulgare L.) in a single Illumina HiSeq 2000 lane. Using a newly designed parallelized computational pipeline, we obtained sequence assemblies of individual BACs that consist, on average, of eight sequence scaffolds and represent >98% of the genomic inserts. Our BAC assemblies are clearly superior to a whole‐genome shotgun assembly regarding contiguity, completeness and the representation of the gene space. Our methods may be employed to rapidly obtain high‐quality assemblies of a large number of clones to assemble map‐based reference sequences of plant and animal species with complex genomes by sequencing along a minimum tiling path.